The use of active methodologies in the math teaching/learning process aligned to Curricular National Basis (Research, Society and Development, 2020)
The advent of the internet has brought great social, economic, technological, political and cultural changes, causing an impact, including, on education. To keep up with these changes, the school needs to reinvent itself, develop new competences, skills and teaching methodologies, making all this progress and transformation work in its favor. Therefore, the present research project seeks to deepen this new model of making schools. The main theme of the work to be carried out is the use of active methodologies in the teaching / learning process, focusing mainly on the subject of mathematics. It is intended to create roadmaps of activities to insert the methodologies active in the day-to-day of the classroom and assist in the assimilation, by the students, of the proposed contents. Such scripts will make it possible to transform the classroom into a “research center”, in which the student goes in search of the desired information, the desired knowledge and the teacher becomes a mediator, a guide in this teaching / learning process, showing become a student partner. In the development of this work, written sources were used as the basis for investigative work in order to complement the information obtained by the research and discover new aspects for the identified problem. As a result of the researches carried out, it was observed that schools link active methodologies and maker culture to the use of modern equipment and tools, such as 3D printers, Arduino board, laser cutters and robotics kits, however, these methodologies can be worked with few resources, but with a lot of creativity. Therefore, 3 activity suggestions were developed as a model for the development of active methodologies in the classroom. That said, it is concluded that these methodologies are only possible and achieve success when students become active people in the teaching / learning process, leaving the condition of recipients of information to become knowledge builders. When they have an effective participation in this process, they “learn to learn”, because, it is known that each human being has a different and unique way of learning, therefore, each student will do it at their own pace, in the way that most pleases them , however, all will reach the same goal, assimilate the proposed content.Incluir o resumo em inglês.